Destructive Environmental Discourse: An Author's Writing Strategy in Children's Stories - Jumiati Lanta; Andi Muhamamd Akhmar; Inriati Lewa; M. Nurzin R Kasau (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This article aims to describe the discourse of the destructive environment found in the book Indonesian Children's Stories of Choice and explain the presence of destructive environmental discourses as an author's writing strategy. Environmental discourse is a subject of special attention in studying language related to the environment. This study uses the Ecolinguistic theory of the story we lived by Arran Stibbe. Environment discourse is stories that live in a community environment that influences and even determines one's mind. The environment consists of constructive and descriptive discourse. This study focuses on destructive environmental discourse, i.e., disasters containing information that violates or opposes environmental conservation values. The results of this study indicate that destructive environments are one of the authors' writing strategies for punishing characters in stories that contradict the environmental values of intelligence. In addition, the discourse of environmental destruction is created to be the reason for the presence of the discourses of resistance that are constructive and on the side of the wisdom of the environment. This study concludes that the authors use the environmental disasters as part of the message of the story to be known so as not to be done or followed by readers, especially readers from among children.